Strategic entrepreneurship increase innovation, competition, employment, and economic development (International Journal of Scientific Research and Management (IJSRM), 2017)
Strategic entrepreneurship is predicated on the combination of entrepreneurship and strategic management. Strategic entrepreneurship could be a new approach in management literature. Moreover, today’s business world needs an orientation towards strategic entrepreneurship. Strategic entrepreneurship is a necessity for corporations to form most wealth. During this study, strategic entrepreneurship and strategic management are analyzed.